Investigation of the airborne particulate matter concentration trend changes in Mashhad by using meteorological data during 2010-2015 - Elham Asrari; maryam Paydar (Mashhad University of Medical Sciences, 2018)
Abstract  Background and Purpose: Air pollution problem in metropolitan's city caused by different sources pollutants. Dispersion of air pollutants in many city of Iran such Mashhad increased. This study aimed to investigate the trend of particular matter concentration changes with weather data in Mashhad air. Materials and Methods: In this descriptive cross - sectional study, data were collected from 11 monitoring stations and synoptic stations in Mashhad during 2010-2016. Daily average concentration (PM 10, PM2.5) was calculated and then relations between pollutant and metrological data analyzed by Spss18 software. Findings: The results showed that the maximum concentrations of particle matter occurred in october and autumn season. Numbers of unhealthy days has been increased during the years 2011-2013, decreased in 2014 - 2015 and increased again in 2016. The variation of PM10 and PM2.5 is significant with season, month and year (P